2022
DOI: 10.3390/v14061137
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Tropism and Sequelae of SARS-CoV-2 Infection

Abstract: The extrapulmonary manifestation of coronavirus disease-19 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), became apparent early in the ongoing pandemic. It is now recognized that cells of the cardiovascular system are targets of SARS-CoV-2 infection and associated disease pathogenesis. While some details are emerging, much remains to be understood pertaining to the mechanistic basis by which SARS-CoV-2 contributes to acute and chronic manifestations of COVID-19. This knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 124 publications
0
6
0
1
Order By: Relevance
“…Reports have indicated that the ongoing evolution of SARS-CoV-2 variants is associated with various cardiovascular diseases ( 39 ). The acute phase of COVID-19 may involve cardiac manifestations including acute coronary syndrome, myocarditis, pericarditis, heart failure, and arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Reports have indicated that the ongoing evolution of SARS-CoV-2 variants is associated with various cardiovascular diseases ( 39 ). The acute phase of COVID-19 may involve cardiac manifestations including acute coronary syndrome, myocarditis, pericarditis, heart failure, and arrhythmias.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact pathophysiological events underlining this cardiovascular complication are not well known, the pathogenesis of COVID-19-induced myocardial inflammation has been proposed to be due to a combination of a direct virally induced cardiomyocyte damage, an overactive immune response to infected cardiac muscle cells and an overproduction of proinflammatory cytokines [ 14 , 21 ]. The similarity in SARS-CoV-2 infection with those induced by other coronaviruses, namely MERS-CoV and SARS-CoV-1, whose viral RNAs were detected in both animal and human heart samples, suggests that even the new member of the Coronaviridae family may possess cardiotropism, meaning that cardiovascular tissues are susceptible to SARS-CoV-2 infection [ 14 ]; SARS-CoV-2 tropism for myocardial cells might be an important determinant of COVID-19-related myocarditis and the viral persistence in the myocardium [ 76 ].…”
Section: Role Of Cardiovascular Factors (Ace2 and Raas) In The Pathog...mentioning
confidence: 99%
“…También se ha observado afectación vascular, manifestándose como embolia pulmonar, trombosis venosa profunda, accidentes cerebrovasculares e isquemia de extremidades 15,16 . El virus tiene un claro tropismo por el sistema cardiovascular y es capaz de infectar cardiomiocitos y pericitos, causando una pérdida de la estructura del sarcómero y muerte celular 17 . Adicionalmente, la COVID-19 puede inducir daño directo al miocardio debido a hipoxemia, hipercoagulabilidad que conduce a trombosis, disfunción microvascular y una tormenta de citocinas, resultando en la desestabilización de la placa aterosclerótica 18 .…”
Section: Introductionunclassified